Adhesive composition with gel content based on crosslinking through ketone or aldehyde groups

CN112004878BActive Publication Date: 2026-10-13BASF SE
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN201980026439.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-04-20
Filing Date
2019-04-10
Publication Date
2026-10-13
Estimated Expiration
2039-04-10

Smart Images

  • Figure BDA0002728182290000121
    Figure BDA0002728182290000121
  • Figure BDA0002728182290000202
    Figure BDA0002728182290000202
  • Figure BDA0002728182290000211
    Figure BDA0002728182290000211
Patent Text Reader

Abstract

The present invention relates to an adhesive composition in the form of a polymer aqueous dispersion comprising a tackifier, a compound crosslinking by a ketone or aldehyde group and an adhesive polymer formed by emulsion polymerization of a soft (meth)acrylate monomer, an acid monomer, a monomer comprising a ketone or aldehyde group, styrene and optionally other monomers, wherein the polymerization can occur in the presence of a molecular weight regulator. According to the invention, the adhesive polymer has a specific gel content. The adhesive composition can be used for the preparation of an adhesive label, an adhesive tape or an adhesive film.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention relates to an adhesive composition in the form of a polymer aqueous dispersion, comprising a tackifier, a compound crosslinked via a ketone or aldehyde group, and a pressure-sensitive adhesive polymer formed by emulsion polymerization of a soft (meth)acrylate monomer, an acid monomer, a monomer containing a ketone or aldehyde group, styrene, and optionally other monomers, wherein polymerization may be carried out in the presence of a chain transfer agent. The pressure-sensitive adhesive polymer has a certain gel content. The pressure-sensitive adhesive composition can be used to prepare adhesive labels, adhesive tapes, or adhesive films.

[0002] Pressure-sensitive adhesives used in applications such as adhesive tapes or films are based on polymer solutions in organic solvents and on aqueous polymer dispersions obtainable through emulsion polymerization. There is a desire to increase the use of aqueous systems and avoid the use of organic solvents. However, depending on the application, the adhesive properties of emulsion polymers are not always equivalent to those of adhesive polymers prepared in organic solvents, as evidenced by the approximately 50-60% market share of solvent-based adhesives. Solution polymers are typically largely unbranched and uncrosslinked, have relatively high molecular weights, and form very uniform adhesive films when coated onto substrates, where long polymer chains can entangle together, resulting in relatively high cohesive strength. As a result, emulsion polymerization generally provides polymers with higher degrees of branching and crosslinking compared to solution polymerization. Branching and crosslinking can be measured by measuring gel content. The higher the branching and crosslinking of a polymer, the higher its gel content. Gel content is the proportion of the polymer film prepared from the polymer that is insoluble in methyl ethyl ketone. Film formation by emulsion polymers typically results in heterogeneous films with microscopically detectable interfaces, attributable to the dispersion particles. This generally reduces cohesive strength and impairs water resistance compared to solvent polymers. Since crosslinking in emulsion polymers occurs primarily within the dispersion particles rather than between polymer chains in different dispersion particles, at high gel contents, crosslinking or entanglement of polymer chains beyond the polymer particle interfaces is severely compromised, making it difficult to improve the cohesive strength of pressure-sensitive adhesives based on emulsion polymers. Therefore, it is desirable to avoid side reactions leading to crosslinking or branching during emulsion polymerization. Such side reactions are often unavoidable when polymerizing acrylate monomers very rapidly. During the free radical emulsion polymerization of acrylate monomers, the dispersion particles typically contain a large amount of polymer and only a very small amount of acrylate monomer due to the very rapid reaction of the acrylate monomer. Therefore, free radicals entering the dispersion particles primarily encounter the polymer (e.g., about 95%), while encountering only a very small amount of monomer (e.g., about 5%), leading to undesirable reactions with the polymer.

[0003] These include, for example, the extraction of hydrogen from the polymer chains and subsequent grafting, branching, or crosslinking reactions. Therefore, after the emulsion polymerization of the acrylate monomers terminates, a significant proportion of the polymer chains within the dispersion particles (e.g., about 60-80%, corresponding to the gel content) are bound together, preventing diffusion beyond the particle boundaries during film formation necessary for use as an adhesive. Only a very small fraction (about 20%) of the predominantly linear, soluble polymer chains (which contribute no to the gel content) are able to do so. This limits cohesion in pressure-sensitive adhesive applications.

[0004] By using chain transfer agents, side reactions leading to crosslinking can be reduced during the emulsion polymerization of acrylate monomers. However, the use of chain transfer agents results in short polymer chains with low molecular weights, which in turn imposes undesirable limitations on cohesion in pressure-sensitive adhesive applications.

[0005] It is also possible to reduce side reactions leading to crosslinking during emulsion polymerization by co-using comonomers that react more slowly than acrylate monomers, such as styrene. Compared to emulsion polymerization of pure acrylate monomers, the use of a large amount of styrene allows free radicals entering the dispersion particles to encounter significantly more monomers (e.g., about 50%) and less polymer (e.g., about 50%). However, styrene is a so-called "hard" monomer because it gives the polymer a relatively high glass transition temperature (Tg) (the Tg of polystyrene is about 105 °C), which is detrimental to pressure-sensitive adhesive applications. Pressure-sensitive adhesive polymers typically have very low Tgs, such as -40 °C or lower. A high Tg will lead to undesirable reductions in adhesion and tack. Adding tackifiers can increase tack, but usually at the same time compromises cohesion, making the preparation of high-cohesion pressure-sensitive adhesives using tackifiers a particular challenge.

[0006] Crosslinking agent systems using the reaction of carbonyl groups with dihydrazides in adhesive polymers are known, for example, WO 2017 / 216108, WO 2006 / 066761, EP 3202795, WO 2003 / 01193, EP 900651, and WO 2017 / 125277. These do not involve pressure-sensitive adhesives or polymers with a high gel content (gel0) prior to carbonyl / hydrazide crosslinking. The result of a high gel content (gel0) prior to carbonyl / hydrazide crosslinking is that a high proportion of polymer chains are already crosslinked and therefore cannot diffuse out of the dispersion particles, thus causing (additional) carbonyl / hydrazide crosslinking to occur essentially within the dispersion particles. This severely limits the cohesive strength of the additional crosslinking—the enhancement effect.

[0007] One object of the present invention is to provide a water-based (i.e., organic solvent-free) polymer pressure-sensitive adhesive, preferably in the form of a stable one-component composition, and having good adhesive properties, particularly improved cohesion similar to that of solution polymers without significantly impairing adhesion and tack, and to be produced as simply and cost-effectively as possible.

[0008] This invention provides an adhesive composition in the form of a polymer aqueous dispersion, comprising...

[0009] (a) at least one tackifier

[0010] (b) At least one compound A, which contains at least two functional groups capable of cross-linking with a ketone group or an aldehyde group;

[0011] (c) At least one pressure-sensitive adhesive polymer formed by emulsion polymerization of the following substances:

[0012] (i) at least 60% by weight of at least one soft (meth)acrylate monomer, which, based on the total amount of monomers, has a glass transition temperature below 0°C when polymerized into a homopolymer.

[0013] (ii) 0.1% to 10% by weight of at least one monomer having at least one acid group, based on the total amount of monomers.

[0014] (iii) At least 5% and less than 20% by weight of styrene, based on the total amount of monomers.

[0015] (iv) 0.3% to 5% by weight, preferably 0.4% to 3% by weight, of at least one alkene-type unsaturated compound K having at least one functional group selected from ketone and aldehyde groups, based on the total amount of monomers.

[0016] (v) optionally different from the other monomers in (i) to (iv),

[0017] However, monomers with at least two non-conjugated polymerizable vinyl groups are excluded.

[0018] The polymerization is carried out in the presence of 0 to 1 part by weight of chain transfer agent per 100 parts by weight of monomer.

[0019] After the film is formed on the substrate, the gel content of the pressure-sensitive adhesive polymer is [not specified]. tot At least 80% by weight, based on a polymer membrane prepared from a pressure-sensitive adhesive polymer.

[0020] At least a portion of the gel content is based on the crosslinking of the polymer's ketone or aldehyde groups with compound A, and the gel content of the pressure-sensitive adhesive polymer based on the crosslinking of the polymer's ketone or aldehyde groups with compound A is... KFor at least 30% by weight

[0021] The gel content can also be partly based on covalent irreversible crosslinking unaffected by the crosslinking of the polymer's ketone or aldehyde groups with compound A, and the gel content gel0 of the pressure-sensitive adhesive polymer based on covalent irreversible crosslinking unaffected by the crosslinking of the polymer's ketone or aldehyde groups with compound A is 0% to no more than 50% by weight.

[0022] Prior to crosslinking the ketone or aldehyde groups of the polymer with compound A, the glass transition temperature of the polymer is below 10°C, preferably below -15°C and above -40°C; and

[0023] The film formed by the pressure-sensitive adhesive composition after drying has an adhesion of not less than 10 N / 25 mm, measured as annular adhesion relative to a steel surface at 23°C, 50% relative humidity and a tearoff speed of 300 mm / min.

[0024] Unless otherwise stated, the recorded percentage values ​​of monomer weight are based on the sum of all monomers used in the polymerization in each case.

[0025] Pressure-sensitive adhesives are viscoelastic adhesives that cure into a film that maintains permanent tack and adhesion at room temperature (20°C) in a dry state. Bonding to the substrate is achieved immediately by applying gentle pressure.

[0026] The names “(meth)acrylic acid” or “(meth)acrylate” and similar names are sometimes used below as abbreviations for “acrylic acid or methacrylic acid” or “acrylate or methacrylate”. In the names (meth)acrylate Cx alkyl ester and similar names, x indicates the number of carbon atoms in the alkyl group.

[0027] A single-component adhesive is an adhesive to which no other components are added before application and which is stable for storage, wherein the viscosity change after 5 days of storage at 20°C is preferably less than 100%, based on an initial viscometer. The proportion of agglomerates (which can be removed by using a filter with a 250 μm mesh size) is preferably no more than 5% by weight, based on the solids content of the dispersion. Viscosity was measured using a cone and plate rotational viscometer (e.g., an Anton Paar rheometer “MCR 301”, measurement setting CP25-1-SN12203) at 23°C and a constant shear rate of 1 s⁻¹. -1 Measurements were taken with a gap width d = 0.05 mm.

[0028] Glass transition temperatures were determined by differential scanning calorimetry (ASTM D 3418-08, midpoint temperature). The glass transition temperatures of the polymers in the polymer dispersion were obtained when evaluating the second heating profile (heating rate 20 °C / min).

[0029] The gel content was measured by preparing a polymer membrane from the polymer dispersion and drying it at room temperature (20°C) for one day and then at 50°C for four days. This membrane was then mixed with 99 times its mass of methyl ethyl ketone and stored at room temperature for four days. It was then filtered through a balanced 125 μm Perlon filter, and the filter was dried at room temperature until solvent-free, followed by a further drying at 50°C for one hour. The gel fraction, the portion insoluble in methyl ethyl ketone, was determined by reweighing.

[0030] Total gel content of pressure-sensitive adhesive polymer tot The gel content (gel0) of the pressure-sensitive adhesive polymer was determined after the addition of compound A and after film formation, drying, and curing of the polymer film. It is based on the covalent irreversible crosslinking of the pressure-sensitive adhesive polymer, unaffected by the crosslinking of the polymer's ketone or aldehyde groups with compound A. The gel content (gel0) of the pressure-sensitive adhesive polymer was determined after film formation and drying without the addition of compound A. k It's a gel tot The difference between gel0 and gel is gel k =gel tot -gel0.

[0031] Total gel content tot Optionally, an additional gel content based on the reversible cross-linking via metal salts may be included. M .

[0032] In this case, gel tot =gel0+gel K +gel M .

[0033] This reversible crosslinking is not achieved through covalent bonds, but rather through ionic bonds or the formation of complexes between the acid groups of the polymer and at least divalent metal cations. Based on the reversible crosslinking via metal salts, the gel content... M For example, 0% to 40% by weight, 0% to 20% by weight, or 0% to 10% by weight, preferably 0% by weight.

[0034] Metal salt crosslinking can be achieved by adding a suitable metal salt after polymerization. Suitable metal salts are, for example, those containing the metal cation Al. 3+ Zn 2+ Ti4+ Ca 2+ Fe 2+ Fe 3+ and Zr 4+ Suitable counterions are, for example, acetylacetonate, hydroxide, oxalate, lactate, glycinate, acetate, and carboxyl groups, or acrylate oligomers containing 2-(methacryloyloxy)ethyl acetoacetate groups with a molar mass up to 50,000 g / mol. Suitable metal salts are, for example, aluminum acetylacetonate Al(acac)3, diisopropoxybis(acetylacetonate)titanium Ti(acac)2OiPr2, diammonium bis[carbonyl-O]-dihydroxyzirconate (20), ferric oxalate (II), calcium hydroxide, or zinc hydroxide, such as Zn(OH)2 / NH3. The metal salt is preferably selected from zinc and aluminum salts, preferably acetylacetonate salts, especially Al(acac)3. Preferred metal salts have a water solubility of less than 10 g / L (at 25°C).

[0035] Crosslinking of metal salts can also be achieved by directly incorporating the metal salt during emulsion polymerization through copolymerization with a suitable organometallic comonomer. The amount of such organometallic comonomer is preferably from 0% to 3% by weight, for example from 0.1% to 2.5% by weight, based on the sum of all monomers. Suitable organometallic comonomers are, for example, aluminum acrylate Al(AS)3, aluminum methacrylate Al(MAS)3, zinc acrylate Zn(AS)2, zinc methacrylate Zn(MAS)2, titanium acrylate (IV), and titanium methacrylate (IV). Preferably, no organometallic comonomer is used.

[0036] The amount of the soft (meth)acrylate monomer (i) is at least 60% by weight, preferably at least 65% by weight, for example 65% to 94% by weight or 80% to 93% by weight. The soft monomer (i) is preferably selected from acrylates, especially acrylic acid C2 to C3. 10 Alkyl esters, or C4 to C5 acrylic acid 10 Alkyl esters, or C4 to C8 alkyl esters of acrylate. Suitable examples include ethyl acrylate, n-butyl acrylate, n-hexyl acrylate, heptyl acrylate, octyl acrylate, and 2-ethylhexyl acrylate, as well as mixtures of these monomers. Ethyl acrylate, n-butyl acrylate, and 2-ethylhexyl acrylate, and mixtures thereof are preferred, with n-butyl acrylate and 2-ethylhexyl acrylate, and mixtures thereof, being particularly preferred.

[0037] The pressure-sensitive adhesive polymer is prepared from another monomer type (ii). The amount of this monomer type (ii) present can be from 0.1% to 10% by weight, preferably from 0.2% to 8% by weight, or from 0.5% to 6% by weight, based on the total amount of monomers used to prepare the polymer. Monomer (ii) is a monomer having at least one acid group (acid monomer), i.e., an olefinically unsaturated acid or an olefinically unsaturated anhydride, and monomer (ii) can be polymerized via a free radical polymerization reaction. Suitable acid monomers are, for example, olefinically unsaturated carboxylic acids, olefinically unsaturated sulfonic acids, and vinylphosphonic acids. Preferably, the olefinically unsaturated carboxylic acids used are α,β-monoolefinically unsaturated monocarboxylic acids and dicarboxylic acids containing 3 to 6 carbon atoms in the molecule. Examples are acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, vinylacetic acid, and vinyllactic acid. Examples of suitable olefinically unsaturated sulfonic acids include vinylsulfonic acid, styrenesulfonic acid, acrylamide methylpropane sulfonic acid, sulfopropyl acrylate, and sulfopropyl methacrylate. Preferred materials include acrylic acid, methacrylic acid, itaconic acid, and mixtures thereof, with methacrylic acid being particularly preferred.

[0038] Pressure-sensitive adhesive polymers are made, in particular, from styrene. The amount of styrene (iii) is at least 5% by weight and less than 20% by weight, preferably 6% to 19% by weight, or 7% to 18% by weight, based on the total amount of monomers.

[0039] The pressure-sensitive adhesive polymer is prepared from at least one olefinically unsaturated compound K having at least one functional group selected from ketone and aldehyde groups. The amount of monomer K is 0.3% by weight to no more than 5% by weight, preferably 0.3% by weight to no more than 4% by weight or 0.4% by weight to no more than 3% by weight, based on the total amount of monomer. Compound K is, for example, acrolein, methacrolein, vinyl alkyl ketones having 1 to 20, preferably 1 to 10, carbon atoms in the alkyl group, formyl styrene, alkyl (meth)acrylates having one or two ketone or aldehyde groups or one aldehyde group and one ketone group in the alkyl group, wherein the alkyl group preferably contains a total of 3 to 10 carbon atoms, such as (meth)acryloyloxyalkylpropionaldehyde, for example, as described in DE-A2722097. Furthermore, suitable alternatives include N-oxoalkyl (meth)acrylamides, for example, known in DE-A 2 061 213 or DE-A 2 207209, such as those with the following formulas.

[0040] RC(=O)-R'-NH-C(=O)-CR"=CH2,

[0041] R and R′ represent hydrogen or a hydrocarbon group (preferably alkyl) having 1 to 10 carbon atoms, and R′ represents a hydrocarbon group (preferably alkylene) having 2 to 15 carbon atoms. Acetylacetyl acrylate, acetylacetoxyethyl acrylate, and especially diacetone acrylamide are particularly preferred.

[0042] Alternatively, monomers (v) other than monomers (i) to (iv) may be used. Other monomers (v) are copolymerizable olefinically unsaturated compounds. The amount of the optional monomer (v) is preferably from 0% to no more than 10% by weight, 0.1% to 10% by weight, 1% to 10% by weight, or 1% to no more than 8% by weight, based on the total amount of monomers. Monomer (v) is preferably a monomer different from monomers (i) to (iv), selected from C1 to C20 alkyl esters of (meth)acrylic acid, monomers containing hydroxyl groups, vinyl esters of carboxylic acids containing up to 20 carbon atoms, vinyl aromatic compounds having up to 20 carbon atoms, olefinically unsaturated nitriles, vinyl halides, vinyl ethers of alcohols containing 1 to 10 carbon atoms, aliphatic hydrocarbons having 2 to 8 carbon atoms and one or two double bonds, and (meth)acrylamide or mixtures of these monomers. Other monomers include phenoxy glycol mono(meth)acrylate, glycidyl (meth)acrylate, and aminoalkyl (meth)acrylate, such as 2-aminoethyl (meth)acrylate. The alkyl group preferably has 1 to 20 carbon atoms. (Meth)acrylate C1-C 20 Alkyl esters have 1 to 20 carbon atoms in the alkyl group. (Meth)acrylic acid C1-C 10 -Hydroxyalkyl esters have 1 to 10 carbon atoms in the hydroxyalkyl group.

[0043] (Meth)acrylate C1 to C20 alkyl esters are, for example, methyl acrylate and methyl methacrylate. Monomers containing hydroxyl groups are, for example, (meth)acrylate C1-C20 alkyl esters. 10 -Hydroxyalkyl esters. Vinyl esters of carboxylic acids having 1 to 20 carbon atoms are, for example, vinyl acetate, vinyl laurate, vinyl stearate, vinyl propionate, and vinyl tert-carbonate. Considerable vinyl aromatic compounds include vinyltoluene, α-methylstyrene and p-methylstyrene, α-butylstyrene, 4-n-butylstyrene, and 4-n-decylstyrene. Examples of nitriles are acrylonitrile and methacrylonitrile. Vinyl halides are alkene-bonded unsaturated compounds substituted with chlorine, fluorine, or bromine, preferably vinyl chloride and vinylidene chloride. Examples of vinyl ethers include vinyl methyl ether or vinyl isobutyl ether. Vinyl ethers of alcohols containing 1 to 4 carbon atoms are preferred. Suitable hydrocarbons having 4 to 8 carbon atoms and two alkene double bonds are, for example, butadiene, isoprene, and chloroprene.

[0044] Preferred other monomers (v) are methyl acrylate, methyl methacrylate, vinyl esters (especially vinyl acetate), mixtures thereof, and C2 to C10 hydroxyalkyl esters of (meth)acrylate. Methyl acrylate, methyl methacrylate, vinyl acetate, and hydroxypropyl acrylate, and mixtures thereof are particularly preferred.

[0045] Monomers excluded from the preparation of pressure-sensitive adhesive polymers include those having at least two non-conjugated polymerizable vinyl groups, especially those that may lead to branching or crosslinking, thereby increasing gel content. Monomers excluded in this category include, for example, polyfunctional acrylates or polyfunctional methacrylates, particularly di(meth)acrylates having, for example, 2 to 8 carbon atoms in the alkane group, especially ethylene glycol diacrylate, propylene glycol diacrylate, polyethylene glycol diacrylate, hexanediol diacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, tri(meth)acrylates, especially trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane trimethacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, or trimethylolpropane trimethacrylate; divinyl compounds, especially divinyl esters, such as divinylbenzene, divinyl succinate, divinyl adipate, divinyl maleate, divinyl oxalate, divinyl malonate, or divinyl glutarate.

[0046] Before the ketone or aldehyde group of the polymer crosslinks with compound A, the glass transition temperature of the polymer is below 10°C, preferably below -15°C, and preferably above -40°C, particularly from -35°C to below -15°C. By purposefully changing the type and amount of monomers, those skilled in the art can prepare aqueous polymer compositions in which the glass transition temperature of the polymer is within the desired range according to the present invention. This can be guided by the Fox equation. According to Fox (TGFox, Bull. Am. Phys. Soc. 1956 [Ser. II] 1, p. 123, and according to Ullmann's Encyclopedia of Industrial Chemistry, Vol. 19, p. 18, 4th edition, Verlag Chemie, Weinheim, 1980), the glass transition temperature of the copolymer is well approximated by the following formula:

[0047] 1 / T g =x 1 / T g 1 +x 2 / T g 2 +....x n / Tg n ,

[0048] Where x 1 x 2 ....x n T represents the mass fraction of monomers 1, 2, ..., n. g 1 T g 2 ....T g n This is the glass transition temperature, expressed in Kelvin, of the polymer composed of only one of monomers 1, 2, ..., n in each case. The Tg of homopolymers of most monomers... g The values ​​are known and listed, for example, in Ullmann's Encyclopedia of Industrial Chemistry, Vol. A21, p. 169, 5th edition, VCH Weinheim, 1992; other sources of the glass transition temperature of homopolymers are, for example, J. Brandrup, E. H. Mömmergut, Polymer Handbook, 1st edition, J. Wiley, New York, 1966; 2nd edition, J. Wiley, New York, 1975; and 3rd edition, J. Wiley, New York, 1989.

[0049] Chain transfer agents can be used in polymerization. It is preferred not to use chain transfer agents. When chain transfer agents are used, their dosage is preferably at least 0.01 parts by weight of chain transfer agent per 100 parts by weight of monomer, for example, 0.01 to 5 parts by weight, or 0.01 to 3 parts by weight, preferably 0.01 to 0.75 parts by weight, relative to 100 parts by weight of monomer to be polymerized. This allows the molar mass of the emulsion polymer to be controlled / reduced through a chain termination reaction. In this process, the chain transfer agent bonds to the polymer, typically to the chain ends. They can be added continuously or in stages during polymerization.

[0050] Suitable chain transfer agents are, for example, organic compounds containing sulfur in bonded form (e.g., compounds with thiol groups), aliphatic and / or aryliphatic halogen compounds, aliphatic and / or aromatic aldehydes, unsaturated fatty acids (e.g., oleic acid), dienes with non-conjugated double bonds (e.g., divinylmethane, terpineol, or vinylcyclohexene), hydrocarbons with readily abstractable hydrogen atoms (e.g., toluene), organic acids or their salts (e.g., formic acid, sodium formate, ammonium formate), alcohols (e.g., isopropanol), and phosphorus compounds (e.g., sodium hypophosphite). Alternatively, a compatible mixture of the above-mentioned chain transfer agents can be used. Chain transfer agents are typically low molecular weight compounds, with a molecular weight of less than 2000, particularly less than 1000 g / mol. It is advantageous to feed a sub-amount or all of the chain transfer agent into the aqueous reaction medium before initiating free radical polymerization. Furthermore, a sub-amount or all of the free radical chain transfer compound can also be advantageously fed into the aqueous reaction medium along with the monomer during polymerization.

[0051] Organic compounds containing a thiol group include, for example, primary, secondary, or tertiary aliphatic thiols, such as ethanethiol, n-propanethiol, 2-propanethiol, n-butanethiol, 2-butanethiol, 2-methyl-2-propanethiol, n-pentanethiol, 2-pentanethiol, 3-pentanethiol, 2-methyl-2-butanethiol, 3-methyl-2-butanethiol, n-hexanethiol, 2-hexanethiol, 3-hexanethiol, 2-methyl-2-pentanethiol, 3-methyl-2-pentanethiol, 4-methyl-2-pentanethiol, 2-methyl-3-pentanethiol, 3-methyl-3-pentanethiol, 2-ethylbutanethiol, 2-ethyl-2-butanethiol, n-heptanethiol, and their derivatives. Isomers, n-octanethiol and its isomers, n-nonanethiol and its isomers, n-decanethiol and its isomers, n-undecanethiol and its isomers, n-dodecanethiol and its isomers, n-tridecanethiol and its isomers, substituted thiols, such as 2-hydroxyethylthiol, aromatic thiols, such as thiophene, o-methylthiophene, m-methylthiophene, or p-methylthiophene, such as mercaptoalkyl carboxylic acids having 1 to 18 carbon atoms in an alkyl group, such as 2-mercaptoethyl propionate, and all other sulfur compounds described in Polymer Handbook, 3rd edition, 1989, J. Brandrup and EH Immergut, John Wiley & Sons, Part II, pages 133-141. Preferred organic compounds containing sulfur in a bonded form include, in particular, tert-butylthiol, ethyl mercaptophosphate, mercaptoethanol, mercaptopropyltrimethoxysilane, tert-dodecylthiol, thiodiethylene glycol, ethyl thioethanol, di-n-butyl sulfide, diisopropyl sulfide, di-n-octyl sulfide, diphenyl sulfide, diisopropyl disulfide, 2-mercaptoethanol, 1,3-mercaptopropanol, 3-mercaptopropane-1,2-diol, 1,4-mercaptobutanol, mercaptoacetic acid, 3-mercaptopropionic acid, mercaptosuccinic acid, thioacetic acid, and thiourea. Particularly preferred thio compounds are tert-butylthiol, ethyl mercaptophosphate, mercaptoethanol, mercaptopropyltrimethoxysilane, 2-ethylhexyl mercaptoacetic acid (EHTG), isooctyl 3-mercaptopropionate (IMOPA), or tert-dodecylthiol (tDMK).

[0052] Aliphatic and / or aromatic aliphatic halogen compounds include, for example, n-butyl chloride, n-butyl bromide, n-butyl iodide, dichloromethane, dichloroethane, chloroform, bromoform, bromotrichloromethane, dibromodichloromethane, carbon tetrachloride, carbon tetrabromide, benzyl chloride, and benzyl bromide. Aliphatic and / or aromatic aldehydes include, for example, formaldehyde, acetaldehyde, propionaldehyde, and / or benzaldehyde.

[0053] The pressure-sensitive adhesive composition comprises at least one compound A, said compound A containing at least two, particularly two to five, functional groups capable of crosslinking with a ketone or aldehyde group. Compounds capable of crosslinking with a ketone or aldehyde group are, for example, compounds having an acylhydrazine group, a hydroxylamine group, an oxime ether group, or an amino group. Suitable compounds having an acylhydrazine group are, for example, polycarboxylic acid acylhydrazines having a molecular weight preferably up to 500 g / mol. Preferred acylhydrazine compounds are dicarboxylic acid dihydrazines having preferably 2 to 10 carbon atoms. Examples include oxalate dihydrazine, malonate dihydrazine, succinate dihydrazine, glutarate dihydrazine, adipic acid dihydrazine, sebacic acid dihydrazine, maleate dihydrazine, fumarate dihydrazine, itaconic acid dihydrazine, and / or isophthalic acid dihydrazine. Adipic acid dihydrazine, sebacic acid dihydrazine, and isophthalic acid dihydrazine are particularly preferred. Examples of suitable compounds having an amino group are ethylenediamine, propylenediamine, butanediamine, pentanediamine, hexanediamine, diethylenetriamine, triethylenetetramine, polyethyleneimine, partially hydrolyzed polyvinylformamide, ethylene oxide and propylene oxide adducts such as "Jeffamines", cyclohexanediamine and xylenediamine.

[0054] Compound A is preferably a dicarboxylic acid dihydrazide having 2 to 10 carbon atoms, and the monomer (iv) is selected from acetoacetyl (meth)acrylate, acetoacetoxyethyl (meth)acrylate, and diacetone acrylamide. Compound A is particularly preferred to be adipic acid dihydrazide and the monomer (iv) is diacetone acrylamide.

[0055] The crosslinking of the ketone or aldehyde groups of the adhesive polymer can optionally be delayed, for example by using hydrazine as a compound and incorporating a volatile carbonyl compound, or by using a hydrazone formed from an acyl hydrazine and a volatile carbonyl compound as compound A. Preferred volatile carbonyl compounds have boiling points below 100°C, particularly below 70°C. Ketones are preferred, especially acetone and methyl ethyl ketone. The preferred amount of the volatile carbonyl compound used for delayed crosslinking is no more than 1% by weight (the sum of free carbonyl compounds and hydrazone-bonded carbonyl compounds, based on the total composition). For applications where the lowest possible volatile organic compound (VOC) content is important, the pressure-sensitive adhesive composition preferably does not contain volatile carbon compounds.

[0056] The molar ratio of the ketone or aldehyde reactive group of compound A to the ketone and aldehyde groups of monomer (iv) is preferably 1:10 to 2:1, particularly 1:5 to 2:1, especially preferably 1:2 to 2:1, and very particularly preferably 1:1.3 to 1.3:1. It is especially preferred that the ketone or aldehyde reactive group and the ketone and / or aldehyde groups are in equimolar amounts.

[0057] Compounds with functional groups can be added to the composition or to the polymer dispersion at any point in time. In the aqueous dispersion, no crosslinking with ketones or aldehydes occurs. Crosslinking only occurs on the coated substrate during the drying process.

[0058] It has been found that the amount and type of gel content can positively influence adhesive properties. Total gel content (gel content) tot The gel content gel0 is determined by covalent irreversible crosslinking based on the ketone or aldehyde groups of the polymer and compound A, which is unaffected by crosslinking. The gel content gel0 is determined by crosslinking of the ketone or aldehyde groups of the polymer and compound A. K Composition, i.e., gel tot =gel0+gel K .

[0059] Total gel content tot Optionally, an additional gel content based on the reversible cross-linking via metal salts may be included. M .

[0060] In this case, gel tot =gel0+gel K +gel M .

[0061] After film formation on the substrate, the total gel content is... tot The value is at least 80% by weight, preferably at least 85% by weight, based on a polymer membrane prepared from a pressure-sensitive adhesive polymer.

[0062] Gel content based on the crosslinking of the ketone or aldehyde group of the polymer with compound A. K The content is at least 30% by weight, preferably at least 40% by weight or at least 45% by weight, or particularly preferably at least 50% by weight, based on a polymer membrane prepared from a pressure-sensitive adhesive polymer. The gel can be adjusted, for example, by the amount of ketone and aldehyde groups in the polymer and the amount of compound A. K .

[0063] The gel content gel0, which is covalently irreversibly crosslinked and unaffected by the crosslinking of the ketone or aldehyde groups of the polymer with compound A, can be from 0% by weight to no more than 50% by weight, preferably no more than 40% by weight or no more than 30% by weight, for example, greater than 0% by weight to 40% by weight or 1% by weight to 30% by weight, based on solids content. Gel0 can be adjusted by using a small amount of chain transfer agent and / or by changing the amount of styrene. It is preferred not to use a chain transfer agent.

[0064] A particularly preferred pressure-sensitive adhesive composition in the form of a polymer aqueous dispersion comprises at least one pressure-sensitive adhesive polymer formed by emulsion polymerization of the following substances:

[0065] (i) at least 65% by weight of at least one acrylate monomer selected from n-butyl acrylate and 2-ethylhexyl acrylate, based on the total amount of monomers.

[0066] (ii) 0.5% to 8% by weight of at least one acid monomer selected from acrylic acid, methacrylic acid and itaconic acid, based on the total amount of monomers;

[0067] (iii) 5% to 19% by weight of styrene, based on the total amount of monomers;

[0068] (iv) 0.3% to 5% by weight of at least one olefinic unsaturated compound having at least one ketone group, based on the total number of monomers, wherein the olefinic unsaturated compound is selected from acetoacetyl (meth)acrylate, acetoacetoxyethyl (meth)acrylate and diacetone acrylamide;

[0069] (v) 0% to 10% by weight of monomers other than monomers (i) to (iv), selected from the total number of monomers, based on the following: (meth)acrylic acid C1 to C20 alkyl esters, monomers containing hydroxyl groups, vinyl esters of carboxylic acids containing up to 20 carbon atoms, vinyl aromatic compounds having up to 20 carbon atoms, olefinic unsaturated nitriles, vinyl halides, vinyl ethers of alcohols containing 1 to 10 carbon atoms, and aliphatic hydrocarbons having 2 to 8 carbon atoms and one or two double bonds.

[0070] The gel content of the pressure-sensitive adhesive polymer is... tot At least 80% by weight, based on polymer membrane.

[0071] The gel content of the pressure-sensitive adhesive polymer based on the crosslinking of the ketone or aldehyde group of the polymer with compound A is [gel content]. K The gel content gel0 of the pressure-sensitive adhesive polymer is greater than 0% by weight and up to 30% by weight, and is based on covalent irreversible crosslinking rather than crosslinking of the polymer's ketone or aldehyde group with compound A, and wherein the glass transition temperature of the pressure-sensitive adhesive polymer is below -15°C.

[0072] The polymer dispersions used according to the present invention can be obtained by free radical emulsion polymerization of an olefinically unsaturated, free radical polymerizable compound (monomer). Emulsion polymerization involves polymerizing the olefinically unsaturated compound (monomer) in water, using ionic and / or nonionic emulsifiers and / or protective colloids or stabilizers as surfactants to stabilize monomer droplets and subsequently polymer particles formed from the monomers. The surfactant is typically used in amounts of 0.1 to 10 parts by weight, preferably 0.2 to 5 parts by weight, based on 100 parts by weight of the monomer to be polymerized.

[0073] A detailed description of suitable protective colloids can be found in Houben-Weyl, *Methods of Organic Chemistry*, Vol. XIV / 1, *Macromolekulare Stoffe*, Georg-Thieme-Verlag, Stuttgart, 1961, pp. 411-420. Useful emulsifiers include anionic, cationic, and nonionic emulsifiers. As surfactants, emulsifiers with molecular weights opposite to those of the protective colloid, typically below 2000 g / mol, are preferred. When using mixtures of surfactants, the components must, of course, be compatible with each other; in case of doubt, this can be verified based on several preliminary tests. Anionic and nonionic emulsifiers are preferred as surfactants. Commonly used accompanying emulsifiers include, for example, ethoxylated fatty alcohols (EO degree: 3 to 50, alkyl: C8 to C1). 36 ), ethoxylated monoalkylphenols, dialkylphenols and trialkylphenols (EO degrees: 3 to 50, alkyl: C4 to C9), alkali metal salts of dialkyl esters of sulfosuccinic acids, and alkyl sulfates (alkyl: C8 to C9). 12 ), ethoxylated alkanols (EO degree: 4 to 30, alkyl: C 12 To C 18 ), ethoxylated alkylphenols (EO degree: 3 to 50, alkyl: C4 to C9), alkyl sulfonic acids (alkyl: C 12 To C 18 ) and alkyl aryl sulfonic acids (alkyl: C9 to C9) 18 Alkali metal salts and ammonium salts.

[0074] Other suitable emulsifiers are compounds of the following general formula.

[0075]

[0076] R5 and R6 are hydrogen or C4 to C14 alkyl groups, but not both hydrogen, and X and Y may be alkali metal ions and / or ammonium ions. Preferably, R5 and R6 are straight-chain or branched alkyl groups or hydrogen groups having 6 to 18 carbon atoms, particularly straight-chain or branched alkyl groups having 6, 12, and 16 carbon atoms, wherein R5 and R6 are not both hydrogen. X and Y are preferably sodium, potassium, or ammonium ions, with sodium being particularly preferred. Particularly advantageous compounds are those in which X and Y are sodium, R5 is a branched alkyl group having 12 carbon atoms, and R6 is hydrogen or R5. Industrial mixtures containing 50 to 90% by weight of the monoalkylated product are typically used. Suitable commercial emulsifiers include, for example, 2A1, NP 50 OC50, Emulgator 825, Emulgator 825S, OG, NSO, 904S I-RA, E 3065 FES 77 AT 18 VSL, NPS 25. For the present invention, ionic emulsifiers or protective colloids are preferred. Ionic emulsifiers are particularly preferred, especially salts and acids, such as carboxylic acids, sulfonic acids, and sulfates, sulfonates, or carboxylates. In particular, mixtures of ionic and nonionic emulsifiers can also be used.

[0077] Polymerization reactions can also occur in the presence of protective colloids. Protective colloids are polymeric compounds that, upon solvation, bind a large amount of water and stabilize dispersions of water-insoluble polymers. Unlike emulsifiers, they typically do not reduce the interfacial surface tension between polymer particles and water. The number-average molecular weight of protective colloids is, for example, higher than 1000 g / mol.

[0078] Emulsion polymerization can be initiated using water-soluble initiators. Examples of water-soluble initiators include, for instance, ammonium and alkali metal salts of persulfate, such as sodium persulfate; hydrogen peroxide; or organic peroxides, such as tert-butyl hydroperoxide. Also suitable as initiators are so-called reduction-oxidation (redox) initiator systems. Redox initiator systems consist of at least one reducing agent, typically inorganic, and an organic or inorganic oxidizing agent. The oxidizing component is, for example, the emulsion polymerization initiators mentioned above. The reducing component is, for instance, an alkali metal salt of sulfurous acid, such as sodium sulfite or sodium bisulfite; an alkali metal salt of disulfurous acid, such as sodium disulfite; bisulfite addition compounds of aliphatic aldehydes and ketones, such as acetone bisulfite; or a reducing agent, such as hydroxymethylsulfinic acid and its salts or ascorbic acid. Redox initiator systems can be used with soluble metal compounds, the metal component of which can exist in multiple valence states. Common redox initiator systems include, for example, ascorbic acid / ferric(II) sulfate / sodium persulfate, tert-butyl hydroperoxide / sodium metabisulfite, and tert-butyl hydroperoxide / Na-hydroxymethylsulfinic acid. Individual components, such as the reducing component, can also be mixtures, such as a mixture of the sodium salt of hydroxymethylsulfinic acid and sodium metabisulfite.

[0079] The initiator is typically used in the form of an aqueous solution, with the lower concentration limit determined by the acceptable amount of water in the dispersion and the upper concentration limit determined by the solubility of the corresponding compound in water. The initiator concentration is typically 0.1 to 30% by weight, preferably 0.5 to 20% by weight, more preferably 1.0 to 10% by weight, based on the monomer to be polymerized. A variety of different initiators can also be used in emulsion polymerization.

[0080] Emulsion polymerization is typically carried out at 30 to 130°C, preferably 50 to 95°C. The polymerization medium may consist of water alone, or a mixture of water and a water-miscible liquid such as methanol. Water alone is preferred.

[0081] Emulsion polymerization can be carried out in a batch process or a feed process, including segmented or gradient operation modes of the feed process. The feed process is preferred, in which a portion of the polymerization batch is first added, heated to the polymerization temperature, and polymerization begins. The remaining portion of the polymerization batch is then typically fed in through multiple spatially separated feeds, one or more of which contain monomers in pure or emulsion form. This feeding is carried out continuously, segmentally, or according to a concentration gradient, while maintaining polymerization within the polymerization zone.

[0082] In polymerization, polymer seeds can be added first to, for example, more effectively control particle size. Polymerization is preferably seed-controlled, i.e., carried out in the presence of polymer seeds (seed latex). Seed latex is an aqueous dispersion of finely divided polymer particles having an average particle size preferably of 20 to 40 nm. The amount of seed latex used is preferably 0.01 to 0.5 parts by weight, particularly preferably 0.03 to 0.3 parts by weight, based on 100 parts by weight of monomer. Suitable seed latexes are, for example, polystyrene-based or polymethyl methacrylate-based latexes. A preferred seed latex is a polystyrene seed.

[0083] The method of adding initiators to the polymerization vessel during free radical aqueous emulsion polymerization is known to those skilled in the art. They can be added entirely to the polymerization vessel initially, or continuously or in stages at the rate of consumption during the free radical aqueous emulsion polymerization. This depends particularly on the chemical properties of the initiator system and the polymerization temperature. Preferably, a portion is added initially, with the remainder fed into the polymerization zone at the rate of consumption. To remove residual monomer, the initiator is typically added after the actual emulsion polymerization has terminated (i.e., after the monomer conversion is at least 95%). In the feed method, the components can be added to the reactor from the top, side, or bottom through the bottom of the reactor.

[0084] Emulsion polymerization typically provides a polymer aqueous dispersion with a solids content of 15% to 75% by weight, preferably 40% to 75% by weight, or 40% to 60% by weight, particularly preferably not less than 50% by weight. For high reactor space-time yields, dispersions with very high solids content are preferred. To achieve a solids content >60% by weight, a bimodal or multimodal particle size distribution should be established, as otherwise the viscosity would become excessively high and the dispersion would be difficult to handle. New batches of particles can be prepared, for example, by adding a seed (EP 81083), by adding an excess of emulsifier, or by adding a microemulsion. Another advantage of high solids content accompanied by low viscosity is improved coating properties. The preparation of new or multiple batches of particles can be carried out at any point in time, depending on the particle size distribution desired for achieving low viscosity. The polymer thus prepared is preferably used in its aqueous dispersion form. The particle size distribution of the dispersion can be unimodal, bimodal, or multimodal.

[0085] Neutralization of the acid groups in the polymer is preferably carried out by feeding a neutralizing agent during or after polymerization, wherein the acid groups are wholly or partially neutralized by feeding a base. The neutralizing agent can be added, for example, in a separate feed, simultaneously with the monomer mixture. After all monomers have been fed, it is preferable that the amount of neutralizing agent necessary for neutralization present in the polymerization reactor is at least 10%, preferably 10% to 100% or 25% to 90% of the acid equivalent. Ammonia is a particularly preferred neutralizing agent. The pH of the polymer dispersion is preferably adjusted to a pH greater than 4.5, more specifically to a pH of 5 to 8.

[0086] The pressure-sensitive adhesive composition comprises at least one tackifier (tackifying resin). The amount of tackifier is preferably 5 to 40 parts by weight, based on 100 parts by weight of the adhesive polymer. The tackifier is a polymer or oligomer additive used in adhesive polymers or generally in elastomers, said additive increasing their auto-adhesiveness (tack, inherent tack, self-adhesion) so that they adhere firmly to a surface after brief, slight contact pressure. Tackifiers include, for example, natural resins, such as rosin resins and their derivatives formed by disproportionation or isomerization, polymerization, dimerization, or hydrogenation, or terpene resins. They may be in their salt form (having, for example, a monovalent or polyvalent counterion (cation)), or preferably in their esterified form. The alcohol used for esterification may be monohydroxy or polyhydroxy. Examples include methanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,2,3-propanethiol, and pentaerythritol. In addition, hydrocarbon resins, such as coumarone-indene resins, polyterpene resins, and hydrocarbon resins based on unsaturated CH compounds, such as butadiene, pentene, methylbutene, isoprene, isoprene, divinylmethane, pentene, cyclopentene, cyclopentadiene, cyclohexadiene, styrene, α-methylstyrene, and vinyltoluene, may be used. Tackifiers are known, for example, in Adhesives Age, July 1987, pp. 19-23 or Polym. Mater. Sci. Eng. 61 (1989), pp. 588-592.

[0087] Polyacrylates with low molecular weight are increasingly being used as tackifiers. These polyacrylates preferably have a weight-average molecular weight M. w Less than 50,000, particularly less than 30,000. The polyacrylate preferably contains at least 60% by weight, particularly at least 80% by weight, of (meth)acrylate C1-C8 alkyl esters. Suitable tackifiers include, for example, low molecular weight polymers and oligomers described in WO 2013 / 117428, having a weight average molecular weight of less than 50,000 and a glass transition temperature of not less than -40°C and not more than 0°C, preferably not less than -35°C and not more than 0°C, which can be prepared by emulsion polymerization in the presence of at least one molecular weight regulator and can be prepared from a monomer mixture containing at least 40% by weight of at least one (meth)acrylate C1 to C20 alkyl ester.

[0088] Preferred tackifiers include natural or chemically modified rosin resins. The rosin resins are primarily composed of rosin acid or rosin acid derivatives or their hydrogenated derivatives. The tackifier can be easily added to the polymer dispersion. The tackifier itself is preferably in aqueous dispersion form. The amount of tackifier by weight is preferably 5 to 100 parts, more preferably 10 to 50 parts, based on 100 parts by weight of the polymer (solids / solids).

[0089] Pressure-sensitive adhesive compositions may also contain other additives, such as fillers, dyes, leveling agents, thickeners (preferably associative thickeners), defoamers, crosslinking agents, plasticizers, pigments, or wetting agents. To better wet surfaces, pressure-sensitive adhesives may contain, in particular, wetting aids (wetting agents), such as fatty alcohol ethoxylates, alkylphenol ethoxylates, nonylphenol ethoxylates, polyoxyethylene / polyoxypropylene, or sodium dodecyl sulfonate. The amount of additives is typically 0.05 to 5 parts by weight, particularly 0.1 to 3 parts by weight, per 100 parts by weight of the adhesive polymer (solids).

[0090] The pressure-sensitive adhesive composition preferably contains

[0091] 60-95 parts by weight of pressure-sensitive adhesive polymer,

[0092] 5-40 parts by weight of tackifier and

[0093] Optional 0-10 parts by weight of other ingredients, such as the above-mentioned wetting agents, thickeners, defoamers, etc.

[0094] The pressure-sensitive adhesive composition is preferably a one-component pressure-sensitive adhesive. A one-component adhesive is an adhesive for which an external crosslinking agent (e.g., an isocyanate crosslinking agent) is not added immediately before use.

[0095] After drying, the film formed by the pressure-sensitive adhesive composition has an adhesion of not less than 10 N / 25 mm, measured relative to the loop tack on a steel surface (at 60 g / m² on a 36 μm thick polyethylene terephthalate film). 2 The application rate of the adhesive was measured relative to steel at a tear-off speed of 300 mm / min at 23°C and 50% relative humidity (see Examples for more details).

[0096] After drying, the film formed by the pressure-sensitive adhesive composition has a peel strength relative to the polyethylene surface preferably greater than 5 N / 25 mm (at a density of 60 g / m²). 2 The application rate was measured on a 36 μm thick polyethylene terephthalate film, relative to polyethylene at 23°C and 50% relative humidity, at a tear speed of 300 mm / min (see Examples for more details).

[0097] Pressure-sensitive adhesive compositions can be used to prepare self-adhesive articles. The articles are at least partially coated with a pressure-sensitive adhesive. The adhesive properties can be adjusted so that the self-adhesive articles can be removed again after adhesion. Self-adhesive articles can be, for example, adhesive labels, adhesive tapes, or adhesive films. Suitable carrier materials are, for example, paper, plastic films, and metal foils. The self-adhesive tape of the present invention can be a tape coated with the aforementioned substance on one or both sides. The self-adhesive label of the present invention can be a label made of paper or thermoplastic film. Tapes made of thermoplastic film are particularly preferred. Thermoplastic films considered include, for example, films made of polyolefins (e.g., polyethylene, polypropylene), polyolefin copolymer films, films made of polyesters (e.g., polyethylene terephthalate), polyvinyl chloride films, or polyacetate films. The surface of the thermoplastic polymer film is preferably corona-treated. Foamed carriers are also considered. One side of the label is coated with adhesive. Preferred substrates for self-adhesive articles are paper and polymer films.

[0098] The self-adhesive article has at least a partial coating of pressure-sensitive adhesive according to the invention on at least one surface. The adhesive can be applied to the article by conventional methods such as roller coating, knife coating, or spreading. The application amount is preferably 0.1 to 300 g per square meter, more preferably 2 to 150 g of solids. A drying step is usually performed after application to remove water / solvent. Water can be removed, for example, by drying at 50°C to 150°C. The resulting coated substrate is used, for example, as a self-adhesive article, such as an adhesive label, adhesive tape, or adhesive film. For this purpose, the carrier can be cut into adhesive tape, adhesive label, or adhesive film before or after the application of the adhesive. The sides of the substrate coated with pressure-sensitive adhesive can be covered with release paper (e.g., silicone paper) for later use.

[0099] Substrates on which self-adhesive articles can be advantageously applied can be, for example, metal, wood, glass, paper, or plastic. Self-adhesive articles are particularly suitable for bonding to packaging surfaces, cardboard boxes, plastic packaging, books, windows, moisture barriers, vehicle bodies, tires, or body parts.

[0100] The present invention also relates to the use of the above-described pressure-sensitive adhesive composition in the preparation of adhesive labels, adhesive tapes or adhesive films.

[0101] The present invention also relates to self-adhesive articles coated with the above-described pressure-sensitive adhesive composition.

[0102] The present invention also relates to a method for preparing self-adhesive articles by coating a substrate with the above-described pressure-sensitive adhesive composition. Example

[0103] The raw materials used and their abbreviations are as follows:

[0104] EHA: 2-Ethylhexyl acrylate

[0105] BA: n-Butyl acrylate

[0106] MA: Methyl acrylate

[0107] S: Styrene

[0108] MAA: Methacrylic acid

[0109] AA: Acrylic acid

[0110] DAAM: Diacetone Acrylamide

[0111] ADDH: adipic acid dihydrazide

[0112] BDA-2: Butylene glycol diacrylate (a crosslinking agent used for irreversible covalent crosslinking)

[0113] tDMK: tert-dodecylthiol

[0114] pphm: Parts by weight / 100 parts by weight of monomer (parts / hundred parts of monomer)

[0115] SC: Standard conditions, relative humidity 50%, 1 bar, 23°C

[0116] Examples marked with V...... are comparative examples; examples marked with E...... are examples of the present invention.

[0117] Performance testing

[0118] Determination of gel content

[0119] The polymer dispersion under investigation was used to prepare a polymer membrane. The polymer membrane was dried at room temperature (20°C) for 1 day, and then dried at 50°C for 4 days. The dried membrane was mixed with 99 times its mass of methyl ethyl ketone. The immersed membrane was stored at room temperature for 4 days. The swollen or dissolved membrane was then filtered through a balanced 125 μm Perlon filter. The filter was dried at room temperature until it was free of solvent. It was then dried again at 50°C for 1 hour, and the gel fraction (the solid fraction insoluble in methyl ethyl ketone and remaining in the filter) was determined by weighing.

[0120] Total gel content of adhesive polymers tot The total gel content is the gel content after film formation on the substrate, which includes the gel content formed during polymerization and the gel content formed by crosslinking of the polymer's ketone groups with compound A. To determine the total gel content, the polymer dispersion is added to compound A (adipic acid dihydrazide) before film formation.

[0121] The gel content gel0, based on covalent irreversible crosslinking unaffected by the crosslinking of the polymer's ketone or aldehyde groups with compound A, was determined using a polymer dispersion that did not contain compound A (without adipic acid dihydrazide).

[0122] Gel content based on crosslinking of ketone groups with compound A k It is the difference between the two gel content measurements mentioned above:

[0123] gel K =gel tot -gel0.

[0124] Testing adhesive properties

[0125] To test the adhesive properties, the pressure-sensitive adhesive was applied at approximately 60 g / m². 2 The application rate is applied to the substrate as a carrier. The film was applied to RN 36 (a biaxially stretched film made of polyethylene terephthalate with a thickness of 36 μm) and dried at 90 °C for 5 minutes.

[0126] Unless otherwise specified, dispersions of membranes crosslinked with ADDH were stored for 5 days under standard conditions (23°C, 50% relative humidity), while dispersions of membranes not crosslinked with ADDH were stored for 24 hours under standard conditions, and then the adhesive properties were determined under standard conditions.

[0127] Fast adhesion (loop tack, corresponding to the FINAT test method FTM9)

[0128] Determining rapid adhesion (surface adhesion, also known as ring adhesion) typically involves measuring the force required to remove a substrate from a carrier material coated with an adhesive applied without pressure at a defined tear speed, at 23°C and 50% relative humidity. The test substrate is steel or polyethylene. A test strip, 25 mm wide and 250 mm long, is cut from the adhesive-coated carrier and stored under standard conditions (23°C, 50% relative humidity) for at least 16 hours. The ends of the test strip are folded inwards with the adhesive side facing inwards for approximately 1 cm. The adhesive strip is looped with the adhesive side facing outwards, and the ends are joined together and clamped in the upper jaw of a tensile testing machine. The support of the test substrate is clamped in the lower jaw. The loop of the adhesive strip is moved downwards through the tensile testing machine at a speed of 300 mm / min, thus adhering the adhesive side of the test strip to the substrate without additional pressure. When the lower edge of the upper jaw is 40 mm above the substrate, the tensile testing machine is stopped and immediately moved upwards again. Test results were recorded with a width of N / 25mm. The maximum value (Fmax) displayed on the monitor was read as a measure of surface adhesion. The average of three individual results was taken.

[0129] Peel-off test (corresponding to FINAT test method FTM1)

[0130] Peel strength is a measure of adhesive force measured at 23°C and 50% relative humidity. To determine peel strength, a 25 mm wide test strip is bonded to a test sample made of polyethylene or steel in each case and rolled once with a 1 kg roller. One end is then clamped in the upper jaw of a tensile strain gauge. The adhesive strip is removed from the test surface at a speed of 300 mm / min at a 180° angle, i.e., the adhesive strip is bent and removed parallel to the test sample, and the force required for this is measured. The peel strength is measured as force in N / 25 mm, which is obtained as an average of five measurements. Peel strength is determined 24 hours after bonding. After this time, the adhesive strength has fully developed.

[0131] Shear strength (corresponding to FINAT test method FTM8)

[0132] Shear strength is a measure of cohesive force measured at 23°C and 50% relative humidity. A carrier coated with pressure-sensitive adhesive is cut into test strips 25 mm or 12.5 mm wide. To determine shear strength, the test strips are bonded to steel with a bonded area of ​​25 x 25 mm (measured at 70°C) or 12.5 x 12.5 mm (measured under standard conditions), rolled once with a 1 kg roller, stored for 10 minutes (under standard conditions, 50% relative humidity, 1 bar, 23°C), and then subjected to hanging stress of 1 kg (12.5 x 12.5 mm under standard conditions, SC) or 2 kg (25 x 25 mm at 70°C). Shear strength is measured in minutes until the weight is dropped; the average of five measurements is calculated for each case.

[0133] SAFT test (heat resistance)

[0134] The test strip was bonded to AFERA ​​steel with an bonding area of ​​25x25mm, rolled four times with a 2kg roller, and subjected to a 1kg suspension stress after a contact time of at least 16 hours. During the suspension stress period, the test strip was continuously heated at a rate of 0.5℃ / min, starting from 23℃. The heating temperature reached when the weight was dropped is a measure of the adhesive's heat resistance. The average value was calculated from three measurements in each case.

[0135] Examples E1-E15 and V1-V8

[0136] Here, emulsion polymers prepared from the monomers listed in Table 1 are used, and they are combined with tackifiers. 933E (rosin ester dispersion) was mixed at a weight ratio of 75:25 (solid:solid, polymer to tackifier ratio). The amounts recorded are parts by weight. Examples marked with V... are comparative examples; examples marked with E... are inventive examples.

[0137] Table 1: Emulsion Polymers

[0138]

[0139] 1) Polymerization was carried out in the presence of 0.1 pphm of the chain transfer agent tDMK.

[0140] 2) Calculations were performed for mixtures of BA, EHA, S, and MAA (i.e., excluding DAAM and ADDH).

[0141] 3) Comparative test of polymer 1 according to Example 1 of WO 06 / 066761

[0142] Adhesive films were prepared and adhesive properties (rapid adhesion, peel strength, shear strength, and SAFT heat resistance) were measured. The results are shown in Table 2.

[0143] Table 2: Performance Results

[0144]

[0145] When carbonyl / hydrazide crosslinking is used, examples show that cohesion and heat resistance are significantly increased, while adhesion is only slightly decreased, if any.

[0146] Examples V9 to V11 (comparative) are crosslinked with BDDA and have high gel 0.

[0147] The emulsion polymers prepared using the monomers listed in Table 3 were used here, and with thickeners 933E (rosin ester dispersion) was mixed at a weight ratio of 75:25 (solids:solids, polymer to tackifier ratio). The amounts recorded are parts by weight. Tg: approx. -30°C.

[0148] Table 3: Emulsion polymers crosslinked with BDDA

[0149]

[0150] Adhesive films were prepared and adhesive properties (rapid adhesion, peel strength, shear strength, and SATF heat resistance) were measured. The results are shown in Table 4.

[0151] Table 4: Performance Results

[0152]

[0153] Examples show that, compared to adhesives with high gel0 and already crosslinked during polymerization by monomers (butylene diacrylate, Tables 3 and 4) having at least two non-conjugated polymerizable vinyl groups, adhesives with high gel0 exhibit superior performance. K (Tables 1 and 2) and adhesives that are crosslinked only during film formation via carbonyl and dihydrazide exhibit better cohesive strength (shear strength) and better heat resistance (SAFT), even in terms of total gel content. tot This is also true in comparable cases (Example V11: 89%), i.e., when the total degree of crosslinking is comparable.

Claims

1. A pressure-sensitive adhesive composition in the form of a polymer aqueous dispersion, comprising: (a) at least one tackifier, (b) At least one compound A, comprising at least two functional groups capable of cross-linking with a ketone group or an aldehyde group; (c) At least one pressure-sensitive adhesive polymer formed by emulsion polymerization of the following substances, (i) 65% to 94% by weight of at least one soft (meth)acrylate monomer, based on the total amount of monomers, wherein the soft (meth)acrylate monomer has a glass transition temperature below 0°C when polymerized into a homopolymer, wherein the soft (meth)acrylate monomer is selected from n-butyl acrylate, 2-ethylhexyl acrylate, n-hexyl acrylate, octyl acrylate, heptyl acrylate, and ethyl acrylate. (ii) 0.1% to 10% by weight of at least one monomer having at least one acid group, based on the total amount of monomers. (iii) 7% to 18% by weight of styrene, based on the total amount of monomers, (iv) 0.4% to 3% by weight of at least one alkene-type unsaturated compound K having at least one functional group selected from ketone and aldehyde groups, based on the total amount of monomers. (v) optionally different from the other monomers in (i) to (iv), However, monomers with at least two non-conjugated polymerizable vinyl groups are excluded. The polymerization is carried out in the presence of 0 to 1 part by weight of chain transfer agent per 100 parts by weight of monomer. After the film is formed on the substrate, the gel content of the pressure-sensitive adhesive polymer is [not specified]. tot At least 80% by weight, based on a polymer membrane prepared from a pressure-sensitive adhesive polymer. At least a portion of the gel content is based on the crosslinking of the polymer's ketone or aldehyde groups with compound A, and the gel content of the pressure-sensitive adhesive polymer based on the crosslinking of the polymer's ketone or aldehyde groups with compound A is... K For at least 30% by weight The gel content is partly based on irreversible covalent crosslinking unaffected by the crosslinking of the polymer's ketone or aldehyde groups with compound A, and the gel content gel0 of the pressure-sensitive adhesive polymer based on irreversible covalent crosslinking unaffected by the crosslinking of the polymer's ketone or aldehyde groups with compound A is 1% to no more than 30% by weight, and wherein the glass transition temperature of the polymer is below 10°C prior to the crosslinking of the polymer's ketone or aldehyde groups with compound A; and in, After drying, the film formed by the pressure-sensitive adhesive composition has an adhesion of not less than 10 N / 25 mm, measured as annular adhesion relative to a steel surface at 23°C, 50% relative humidity and a tear speed of 300 mm / min.

2. The pressure-sensitive adhesive composition according to claim 1, wherein the glass transition temperature of the polymer is below -15°C and above -40°C prior to crosslinking the ketone or aldehyde group of the polymer with compound A.

3. The pressure-sensitive adhesive composition according to claim 1, wherein, after drying, the film formed by the pressure-sensitive adhesive composition has a peel strength greater than 5 N / 25 mm, measured relative to a polyethylene surface at 23°C, 50% relative humidity, and a tear speed of 300 mm / min.

4. The pressure-sensitive adhesive composition according to any one of the preceding claims, wherein the pressure-sensitive adhesive polymer is formed from 0.5% to 6% by weight of monomer (ii) based on the total amount of monomers, and wherein the monomer (ii) is selected from acrylic acid, methacrylic acid, itaconic acid and mixtures thereof.

5. The pressure-sensitive adhesive composition according to any one of claims 1-3, wherein the monomer (iv) is selected from acrolein, methacrolein, vinyl alkyl ketones having 1 to 20 carbon atoms in the alkyl group, formyl styrene, alkyl (meth)acrylates having one or two ketone or aldehyde groups in the alkyl group or having aldehyde and ketone groups, N-oxoalkyl (meth)acrylamide, acetoacetyl (meth)acrylate, acetoacetoxyethyl (meth)acrylate, and diacetone acrylamide.

6. The pressure-sensitive adhesive composition according to any one of claims 1-3, wherein compound A is selected from compounds having an acylhydrazine group, a hydroxylamine group, an oxime ether group or an amino group.

7. The pressure-sensitive adhesive composition according to any one of claims 1-3, wherein compound A is a dicarboxylic acid dihydrazide having 2 to 10 carbon atoms, and wherein the monomer (iv) is selected from acetoacetyl methacrylate, acetoacetoxyethyl methacrylate, and diacetone acrylamide.

8. The pressure-sensitive adhesive composition according to any one of claims 1-3, wherein compound A is adipic acid dihydrazide, and wherein monomer (iv) is diacetone acrylamide.

9. The pressure-sensitive adhesive composition according to any one of claims 1-3, wherein the molar ratio of the ketone or aldehyde reactive group of compound A to the ketone and aldehyde groups of compound K is 1:10 to 2:

1.

10. The pressure-sensitive adhesive composition according to claim 9, wherein the molar ratio of the ketone or aldehyde reactive group of compound A to the ketone and aldehyde groups of compound K is from 1:1.3 to 1.3:

1.

11. The pressure-sensitive adhesive composition according to any one of claims 1-3, wherein the optional monomer (v) is used in an amount of 0% to 10% by weight, based on the total number of monomers, and is a monomer different from monomers (i) to (iv), selected from: C1 to C20 alkyl esters of (meth)acrylate, monomers containing hydroxyl groups, vinyl esters of carboxylic acids containing up to 20 carbon atoms, vinyl aromatic compounds having up to 20 carbon atoms, olefinic unsaturated nitriles, vinyl halides, vinyl ethers of alcohols containing 1 to 10 carbon atoms, aliphatic hydrocarbons having 2 to 8 carbon atoms and one or two double bonds, and (meth)acrylamide.

12. The pressure-sensitive adhesive composition according to any one of claims 1-3, wherein polymerization is carried out in the presence of 0.01 to 0.75 parts by weight of chain transfer agent per 100 parts by weight of monomer.

13. The pressure-sensitive adhesive composition according to any one of claims 1-3, wherein the gel content of the pressure-sensitive adhesive polymer based on the crosslinking of the ketone or aldehyde group of the polymer with compound A is [gel content missing]. K It is at least 50% by weight.

14. The pressure-sensitive adhesive composition according to any one of claims 1-3, wherein the pressure-sensitive adhesive composition comprises 5 to 40 parts by weight of at least one tackifier, based on 100 parts by weight of polymer.

15. The pressure-sensitive adhesive composition of claim 14, wherein the tackifier is selected from natural and chemically modified rosin resins.

16. The pressure-sensitive adhesive composition of claim 15, wherein the rosin resin comprises rosin acid or a rosin acid derivative or a hydrogenated derivative thereof.

17. The pressure-sensitive adhesive composition of claim 1, wherein the pressure-sensitive adhesive polymer is formed from: (i) 65% to 94% by weight of at least one acrylate monomer selected from n-butyl acrylate and 2-ethylhexyl acrylate, based on the total amount of monomers. (ii) 0.5% to 8% by weight of at least one acid monomer selected from acrylic acid, methacrylic acid and itaconic acid, based on the total amount of monomers; (iii) 7% to 18% by weight of styrene, based on the total amount of monomers; (iv) 0.4% to 3% by weight of at least one olefinic unsaturated compound having at least one ketone group, based on the total number of monomers, wherein the olefinic unsaturated compound is selected from acetoacetyl (meth)acrylate, acetoacetoxyethyl (meth)acrylate and diacetone acrylamide; (v) 0% to 10% by weight of monomers other than monomers (i) to (iv), selected from the total number of monomers, based on the following: (meth)acrylic acid C1 to C20 alkyl esters, monomers containing hydroxyl groups, vinyl esters of carboxylic acids containing up to 20 carbon atoms, vinyl aromatic compounds having up to 20 carbon atoms, olefinic unsaturated nitriles, vinyl halides, vinyl ethers of alcohols containing 1 to 10 carbon atoms, and aliphatic hydrocarbons having 2 to 8 carbon atoms and one or two double bonds. The gel content of the pressure-sensitive adhesive polymer is... tot At least 80% by weight, based on polymer membrane. The gel content of the pressure-sensitive adhesive polymer based on the crosslinking of the ketone or aldehyde group of the polymer with compound A is [gel content]. K For at least 50% by weight Furthermore, the gel content (gel0) of the pressure-sensitive adhesive polymer, which is based on irreversible covalent crosslinking rather than on the crosslinking of the polymer's ketone or aldehyde groups with compound A, is from 1% by weight to a maximum of 30% by weight. Furthermore, the glass transition temperature of the pressure-sensitive adhesive polymer is below -15℃.

18. Use of the pressure-sensitive adhesive composition according to any one of the preceding claims for the preparation of adhesive labels, adhesive tapes or adhesive films.

19. A self-adhesive article coated with a pressure-sensitive adhesive composition according to any one of claims 1 to 17.

20. A method for preparing a self-adhesive article, carried out by coating a substrate with a pressure-sensitive adhesive composition according to any one of claims 1 to 17.

Citation Information

Patent Citations

  • Novel acrylic fibers and methods for their production

    DE2061213A1

  • New photopolymerizable mixtures for light-sensitive, relief-image-producing recording layers

    DE2207209A1

  • (meth)acryloxy-alkylpropanals, process for their preparation and use thereof

    DE2722097A1

  • Use of aqueous polyacrylic dispersions as laminating adhesive

    EP0900651A1

  • A dielectrophoretic particle concentrator

    WO2003001193A1